Multicultural special education for inclusive classrooms intersectional teaching and learning - Perzigian, Aaron B. T.; Aziz, Nahrin (Routledge, Taylor & Francis Group, 2023)
"This book provides a comprehensive exploration of critical topics in multicultural special education. Filled with case studies, objectives, and summaries to support deeper learning, chapters discuss privilege and power in K-12 school systems, effective and differentiated instruction, culturally competent IEPs and transition plans, and appropriate assessment. Drawing from seminal multicultural education and culturally sustaining pedagogies, this essential text helps educators develop the skills necessary to affirm and honor identities while meeting the instructional needs of culturally diverse students with disabilities"--